2018
DOI: 10.1086/700757
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Paleo-Landscapes: Defining the Land-Use Systems of the Ancient Malayo-Polynesian Homeland

Abstract: This study Cultural layer, beneath shell midden Beta-416882 Charcoal 2810 5 30 1050-895 BC (95.4) This study Cultural layer, beneath shell midden Beta-426160 Animal bone 2860 5 30 1118-929 BC (95.4) This study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…Another direct C14 date of 3,975-3,380 (3,400 ± 125) ybp came from a single rice husk found inside pottery at Andarayan, northern Luzon, Philippines 15 . Other more recent studies have reported charred rice grains in archaeological deposits close to 3,000 ybp in northern Luzon 16 , and additional rice phytolith evidence has been reported previously from Minanga Sipakko and the nearby site of Kamassi in Sulawesi 17 .…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Another direct C14 date of 3,975-3,380 (3,400 ± 125) ybp came from a single rice husk found inside pottery at Andarayan, northern Luzon, Philippines 15 . Other more recent studies have reported charred rice grains in archaeological deposits close to 3,000 ybp in northern Luzon 16 , and additional rice phytolith evidence has been reported previously from Minanga Sipakko and the nearby site of Kamassi in Sulawesi 17 .…”
supporting
confidence: 64%
“…In ISEA, red-slipped thin-walled pottery has been dated at several sites in Taiwan to as early as 4,800-4,200 ybp. A related pottery tradition thereafter appeared in the northern Philippines around 4,200-4,000 ybp 16,23,24,31,32 . Over the next few centuries, this archaeological signature spread southwards into the central and southern Philippines, eastern Indonesia [33][34][35][36] , and the western islands of Remote Oceania 37 .…”
Section: Discussionmentioning
confidence: 99%
“…1) could not support rice field systems comparable in scale to those that developed in coastal areas. Outside the southeastern Asian mainland, islands such as Taiwan and the Philippines also lacked coastal plains suitable for extensive paddy rice cultivation during the mid-Holocene (16,26). Neolithic rice remains, such as those found in sites along paleoshorelines in west Taiwan, indicate that some small wetlands on the edge of islands may have encouraged the practice of Neolithic wet rice farming (26).…”
Section: Discussionmentioning
confidence: 99%
“…South of the Yangtze there are currently no more than 20 sites yielding direct archaeobotanical evidence of rice during the period from ∼5 to 3 ka. There are directly dated carbonized rice remains from several sites but often the evidence can only establish the presence of rice, without offering insight into the cultivation strategies employed ( 14 16 ).…”
mentioning
confidence: 99%
“…He demonstrates that such representations often overlook the complex and highly situated interplay of past investment and land infrastructure that might obstruct even the most ambitious forms of ecological imperialism. This and other archaeological research are moving beyond studies of adaptation to a “natural” environment and instead are seeking to understand how those who strive to shape the environment must work with the materials and the problems—the terraces, the imported soils, the arrays of infrastructure, the concepts of “resources”—that they inherit from the past (Carson and Hung ; Johansen and Bauer ; Quintus ; Vining ; Wilkinson ). Other studies are going further, challenging environmental histories that cast humanity in a central role by imagining and implementing a “multispecies archaeology” that comprises nonhumans, plants, soils, microbes, and DNA (S. Birch ; Given ).…”
Section: Socionature and Political Ecologymentioning
confidence: 99%